The Effect of Lecturer’s Competence and Learning Process Quality on Student’s Satisfaction - Sulistianingsih, Endang; D Hartati, Mursyidah; ., Sumartono; Prihadi, Deddy (International Journal of Engineering and Technology, 2018)
The purpose of the study was to find out the effect of lecturer’s competence and learning process quality on student’s satisfaction. This study was verification research using explanatory survey method. This study used descriptive analysis, classical assumptions test, and multiple regression analysis. The results of the analysis were: 1) there was no effect of lecturers' competence on students' satisfaction, 2) there was a positive effect of learning process quality on student's satisfaction, 3) there was a positive effect of lecturer's competence and learning process on student's satisfaction.  The conclusion of the research is student's satisfaction can be improved by lecturer’s competence and learning process quality development.
Keywords: Lecturer’s Competency; Learning Process; Quality Management; Student’s Satisfaction